CLINICAL-RADIOGRAPHIC CORRELATION OF DEGENERATIVE CHANGES OF THE SPINE - SYSTEMATIC REVIEW - Vialle,Emiliano Neves (2016)
ABSTRACT Systematic review of the literature on the evaluation of images of degenerative changes of the spine and its clinical correlation. A systematic literature review was conducted, and the results evaluated for the presence of clinical correlation, as well as the type of imaging method used. The search terms were "Intervertebral Disc Degeneration", "Intervertebral disc", "Classification", "Anulus fibrosus", "Nucleus pulposus", "Lumbar spine", "Degenerative disc disease", "Degeneration", "Zygapophyseal Joint". We also assessed whether there were inter- and intraobserver agreement in the selected works and possible guidelines regarding the treatment and prognosis of patients. Of the 91 reviewed abstracts, 31 articles were selected that met the inclusion criteria. Six articles were related to the cervical spine, 13 to the lumbar spine and 12 were about changes not related specifically to a single segment of the spine. Articles that determined limiting values considered normal were also included, since variations were considered signs of degeneration or pathology. It was not possible to establish the relationship between the changes identified in imaging and the clinical history of patients, either define treatment and prognosis guidelines.